2008
DOI: 10.1001/archsurg.2007.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Preoperative Checklist and Team Briefing Among Surgeons, Nurses, and Anesthesiologists to Reduce Failures in Communication

Abstract: Interprofessional checklist briefings reduced the number of communication failures and promoted proactive and collaborative team communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
335
1
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(362 citation statements)
references
References 18 publications
13
335
1
13
Order By: Relevance
“…Completion of the sign-in, time-out, and sign-out checklists require a formal pause in patient care with all team members present and communicating. Preoperative team introductions and briefings have been shown to also significantly improve patient safety, team morale, and specific clinical outcomes [16]- [18]. Ali et al conducted a questionnaire study among 37 surgical staff members and reported that 89% of staff believed the WHO safety checklist improved communication and 97% thought the pause highlighted potential patient problems [19].…”
Section: Discussionmentioning
confidence: 99%
“…Completion of the sign-in, time-out, and sign-out checklists require a formal pause in patient care with all team members present and communicating. Preoperative team introductions and briefings have been shown to also significantly improve patient safety, team morale, and specific clinical outcomes [16]- [18]. Ali et al conducted a questionnaire study among 37 surgical staff members and reported that 89% of staff believed the WHO safety checklist improved communication and 97% thought the pause highlighted potential patient problems [19].…”
Section: Discussionmentioning
confidence: 99%
“…Certain cultural barriers may also play a significant role, such as the presence of hierarchies that can hinder open communication and the related ability to ''speak up'' with concerns, as related in the TO literature. Where these cultural barriers highlight historical descriptions of the doctor-nurse relationship and its effect on patient care, [19][20][21] Critical Conversations provide an opportunity to improve such interdisciplinary relationships by providing a shared tool for direct communication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed improved overall communication as a result of both increased communication [56] and reduced failures of communication [45]. The sign-in, time-out, and sign-out periods prompted by a surgical checklist introduced in a pediatric hospital facilitated communication among operating room staff and, subsequently, identification of ''near miss'' situations [56].…”
Section: Do Safety Checklists Improve Quality Of Surgical Care?mentioning
confidence: 99%
“…The sign-in, time-out, and sign-out periods prompted by a surgical checklist introduced in a pediatric hospital facilitated communication among operating room staff and, subsequently, identification of ''near miss'' situations [56]. The implementation of a surgical checklist in general surgery reduced the mean number of communication failures per procedure from 3.95 to 1.31 as well as reduced the number of communication failures associated with visible negative consequences by 64% [45]. Checklists also enhanced processes of care such as appropriate use of prophylactic antibiotics to reduce surgical site infection [22].…”
Section: Do Safety Checklists Improve Quality Of Surgical Care?mentioning
confidence: 99%